Public-private health partnerships: a strategy for WHO - Buse Kent; Waxman Amalia (Bulletin of the World Health Organization, 2001)
Following early success with a number of high-profile partnerships, WHO is increasingly working with the private for-profit sector. In so doing, the organization finds itself in the maelstrom of a vibrant debate on the roles of public, civic, and commercial entities in society and on the appropriate modes of interaction among them. This paper examines WHO's involvement with the commercial sector, particularly in partnerships. WHO's approach to this sector is outlined and the criticisms levelled at public-private partnerships are reviewed. An indication is given of the steps recently taken by WHO to confront the concerns that have been expressed. The paper argues that partnership between WHO and the commercial sector is inevitable and that it presents considerable opportunities, but also significant risks, for the organization and for public health. A strategy is proposed for directing the debate on issues critical to WHO and its role in the promotion and protection of public health.